Cell [compact disc, unabridged] - Cook, Robin, 1940- (Penguin Group, 2014)
George Wilson, M.D., a radiology resident in Los Angeles, is about to enter a profession on the brink of an enormous paradigm shift, foreshadowing a vastly different role for doctors everywhere. George's initial collision with this incredible innovation is devastating. He awakens one morning to find his fiancee dead in bed alongside him, not long after she participated in an iDoc beta test.